ANALISIS KRITIS PERUBAHAN PERAN MEDIA DALAM PERALIHAN DARI BELANJA OFFLINE KE ONLINE : Studi Pasar Tegal Gubug Cirebon - Ninda Nurul Fadhilah; Milatul Zulfa (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
The development of digital media has changed people's consumption patterns from offline to online shopping, which is increasingly prevalent in the digital era. This article reviews the impact of this shift with a focus on the role of new media in shaping consumer preferences towards online shopping. This research uses a descriptive qualitative method that emphasizes on literature studies. New media provides easy access to information, product reviews, and competitive prices, which makes it easier for consumers to switch to e-commerce platforms. Another visible impact is the decline in foot traffic at physical stores, especially small and medium enterprises that find it difficult to compete in operational costs. This shift has also resulted in the loss of social interaction that generally occurs in physical markets, reducing the relationship between sellers and buyers. In addition, online shopping often encourages consumptive and impulsive behavior due to the ease of access. This study emphasizes the importance of technological adaptation for businesses to remain relevant in the rapidly evolving digital marketplace.